Biogenesis of G-protein Mediated Calcium Signaling in Human Megakaryocytes - Dekker, Els den; Gorter, Gertie; Vuurst, Hans van der; Heemskerk, Johan W. M.; Akkerman, Jan-Willem N. (Thrombosis and Haemostasis, 2001)
To understand how platelet signal transduction pathways develop during megakaryocytopoiesis, we isolated human stem cells from umbilical cord blood and cultured the cells in the presence of thrombopoietin (TPO). Based on the early expression of CD61 and late expression of CD42b, immature (CD61+/CD42blow) and mature (CD61+/ CD42bhigh) megakaryocytes were immunomagnetically purified and, together with stem cells (CD34+), characterized for G -protein expression and agonist-induced [Ca2+]i increases. Megakaryocytopoiesis was accompanied by down-regulation of the 43 kDa and 46 kDa variants of G16α, constant expression of Gsα, and up-regulation of Gqα and Giα1/2. The increase in Gq and Gi 1/2 expression was accompanied by an increase in Ca2+ signaling triggered by thrombin and other agonists known to signal to Ca2+ via these G-proteins in platelets. The prostacyclin analog iloprost and TPO also induced [Ca2+]i increases, and the iloprost-induced Ca2+ response disappeared during maturation. These data reveal sharp changes in Ca2+ regulation during megakaryocytopoiesis.
Keywords: Megakaryocytopoiesis; signaling; trimeric G-proteins; calcium